PENGARUH STRUKTUR ORGANISASI, SISTEM PERENCANAAN, SISTEM PELAKSANAAN, DAN PELAPORAN PADA AKUNTANSI PERTANGGUNGJAWABAN TERHADAP PENGENDALIAN BIAYA: Studi Empiris Pada CV. Bintang Utama, Ende - Mahmud, Abdul A; Timba, Tobias; Ismail, Nuraini (Jurnal Riset Ilmu Akuntansi, 2021)
This study aims to determine the effect of organizational structure, planning systems, implementation systems, and partial and simultaneous reporting on cost control. This research is a causal research with a quantitative approach with the object of research at CV. Main Star of Ende. The population in this study were all employees of CV. The main star of Ende, who numbered 33 people. The sample of this research is all employees at CV. Bintang Utama Ende, as many as 33 people. The research data is primary data obtained directly through research questionnaires distributed to research respondents. The variables in this study consisted of independent variables consisting of four variables, namely organizational structure, planning system, implementation system, and reporting, and the dependent variable was cost control. The data analysis used is descriptive statistics, data quality test, classical assumption test and hypothesis test. The conclusion of this study is that both partially and simultaneously the variables of the application of organizational structure, planning systems, implementation systems, and reporting on responsibility accounting have a significant effect on cost control.